A participação do empregado na implantação de um programa de gerência de qualidade total: a região operacional Rio de Janeiro da Embratel - Campos, Clarissa de Souza Monteiro (1996)
Abstract of the dissertation presented to Escola Brasileira de Administração Pública - EBAP, at Fundação Getúlio Vargas - FGV, as part of the requirements for the degree of Master of Public Administration The Employees Participation in a Total Quality Management Program: Operational Division ofEmbratel Rio de Janeiro Clarissa de Souza Monteiro Campos September, 1996 Centro de Formação Acadêmica e Pesquisa Advisor: Professor Paulo Reis Vieira The present work aims to study a Total Quality program, focusing in the employees' engagement in such programo Through the use of a field research, the intention was to gather various opinions about employees' cooperation to the program establishment, observing the acceptance and the engagement of the employees to the Total Quality program philosophy and to the development of a continuous excellence concept in the organization. As an exploratory research, with qualitative characteristics, the field research (?'Pesquisa de Campo') had no intention of making generalizations. Through a qualitative approach, the research meant to gather. during the inquire, descriptive comments to the questionnaire, as well observe the interviewed parties' behavior to the questionnaire issue. In no time was there a concem towards solving given problems, or judging either accurate or contradictive measures of the organization' s TQC program establishment proceedure. The investigator based all its data valuation and application on the hypothesis that: through observed contradictions. one can achieve the needed solutions to the existing problems, and therefore, contradictions should be taken as a starting element to the establishment of a continuous improvement process in the organization. The Total Quality Program establishment experience in the Rio de Janeiro Operation District of Embratel, up to where the investigator's data limitation allowed her to conclude, has more positive aspects, as far as the employees' participation is concemed, than negative ones. The observed limitations of this research are capable of being surpassed if more effort is made in elucidating the program's objective and, especially, explaining what the Program aims to achieve. This procedure would most likely increase the employees' acceptance to the program